Design of Broadband Dispersion Compensating Photonic Crystal Fiber - Habib, Md. Selim; Habib, Md. Samiul; Razzak, S.M.A; Khan, M.A.G (International Journal of Engineering and Technology, 2012)
This paper presents a triangular-lattice photonic crystal fiber for broadband dispersion compensation. The finite element method with perfectly matched absorbing layers boundary condition is used to investigate the guiding properties. The designed dispersion compensating fiber shows that it is possible to obtain a larger negative dispersion coefficient of ?360 ps/(nm.km) at 1.55 ?m, better dispersion slope compensation, better compensation ratio in the entire  telecommunication (1460-1640 nm) band by using a modest number of design parameters and very simple cladding design.